The Different Types of Overtime Work in Nursing and Their Associations With Nurse and Patient Outcomes: A Cross-Sectional Study Protocol - Braiki, Raouaa; Rochefort, Christian (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Université de Montréal, 2025)
Introduction: Nurses often work overtime to fill the shortage of nurses, ensure continuity of care or prevent service breakdowns. Some studies show that working overtime has negative impacts on both nurse and patient outcomes, whereas others suggest that overtime has some beneficial outcomes for patients and nurses. Some authors suggest that these conflicting results across studies could be explained by the type of overtime performed by nurses, an aspect that has received scant research attention. Objective: We aim to examine the associations between the different types of overtime work (voluntary or mandatory), and nurses’ perceptions of nurse and patient outcomes. Method: A provincial electronic cross-sectional survey will be conducted in the province of Quebec, Canada, to examine the associations between nurse overtime work and both nurse and patient outcomes. Discussion and Research Spin-offs: This study will likely provide deeper insights about the different types of overtime and their impacts on both nurse and patient outcomes. This may inform nursing practices and guide nursing union representatives, directors of nursing and government decision-makers.